Analisa Kinerja Heat Recovery Steam Generation Akibat Perubahan Load Turbin Power Generator untuk Proses LNG Hub dan Efisiensi Operasional di Perusahaan Migas - Muchlis, Muchlis; Sariadi, Sariadi; Harunsyah, Harunsyah (Politeknik Negeri Lhokseumawe, 2024)
Problems that occur with the HRSG will be calculated and performed by performance analysis of the equipment. With various methods and formulas that will be used. The aim of the research is to calculate HRSG efficiency before and after cleaning in power generation systems using Matlab software, determine the effect of HRSG efficiency before and after cleaning and understand how to optimize HRSG performance. HRSG efficiency calculations in this research were carried out by comparing the energy flow rate used to evaporate water, both in low pressure steam and high pressure steam and the energy flow rate contained in the exhaust gas from the gas turbine power plant system which is useful in HRSG. HRSG performance calculations based on changes in load for LNG hub operational business processes and operational efficiency in power usage, such as calculating mass balance, calculating energy balance, calculating HRSG performance efficiency in LNG hub operational conditions, calculating HRSG performance efficiency in actual conditions after the event LNG hub process and efficiency of power use in operations, comparison between HRSG performance efficiency in actual conditions and design data efficiency at commissioning. So the results obtained were an efficiency of 61.37% and there was a decrease in performance after being compared with the commissioning design data of 38.32%.